Chasing (macro)elements in microinvertebrates: A new methodological approach for quantitative and qualitative analyses of phosphorus by PIXE (Particle‐Induced X‐Ray Emission) applied to glacier tardigrades - Tereza Novotná Jaroměřská; Vladimír Havránek; David Novotný; Krzysztof Zawierucha; Oleksandr Romanenko; Jakub Štenc; Lenka Vondrovicová; Marie Fayadová; Jakub Trubač (Methods in Ecology and Evolution)
Abstract Microinvertebrates in harsh environments often occupy the highest trophic levels and directly influence the turnover of macroelements. However, the investigation of their body elemental composition is complicated due to their low dry weight or sample size hindering the application of established methodological approaches. We present a new methodological approach for the estimation of body phosphorus (P) in single or multiple microinvertebrate species. As a target model, we chose glacier tardigrades, which are among the top consumers on glacier surfaces, and the nescience of their P content prevents deeper investigations of their contribution to glacier nutrient cycling. We used Particle‐Induced X‐Ray Emission (PIXE) with the application of Proton Elastic Scattering Analysis (PESA) for the estimation of P content (%) per dry weight of individual arctic glacier tardigrades. To test the reliability of the new PIXE–PESA approach, P content was also measured by commonly used ICP‐OES (inductively coupled plasma‐optical emission spectrometry) and the weight of tardigrades was simultaneously estimated by established approaches. The total P, Ca and S concentration and % per dry weight were estimated in 55 tardigrades. The median dry weight was 43 ng. We identified specimens to the lowest taxonomic resolution by light microscopy prior to analysis. The error in the estimation of body P % by the PIXE–PESA approach was approximately 10%. ICP‐OES result met the interquartile range of PIXE results. Dry weight from the PIXE–PESA approach positively correlated with wet weight. Glacier tardigrades revealed a high P concentration compared to other invertebrates and a strong positive correlation in mass % of P to Ca in the bucco‐pharyngeal apparatus and claws. The PIXE–PESA approach is a reliable method for analyses of P and other low‐atomic number (Z) elements (e.g. Ca, S) in microinvertebrates. Since the PIXE–PESA approach reduces time demands and sample size compared to other approaches, it provides new opportunities for elemental analyses in microinvertebrates and facilitates further investigation of intraspecific elemental composition or elemental analyses of cryptic species due to its non‐destructive character. We believe that the PIXE–PESA approach will help to expand the currently limited data on the elemental composition of microinvertebrates and their ecology in a broad range of ecosystems.